Identifikasi Aktivitas Konveksi Menggunakan Model WRF-ARW dan Indeks Stabilitas Atmosfer di Cekungan Bandung: Identifikasi Aktivitas Konveksi Menggunakan Model WRF-ARW dan Indeks Stabilitas Atmosfer di Cekungan Bandung - Al Habib, Abdul Hamid; Hutauruk, Reinhart C. H.; Trilaksono, Nurjanna Joko; Wicaksana, Haryas Subyantara; Choir, Arini Amalia (Jurnal Meteorologi dan Geofisika, 2025)
The Bandung Basin, characterized by complex topography, experiences some of the highest occurrences of heavy rainfall and hail in Indonesia. This study focuses on forecasting convective activity associated with a thunderstorm and heavy rainfall event that triggered flooding in the Pagarsih area, West Java, on 4 October 2022. The spatiotemporal forecast characteristics of convection are assessed using atmospheric stability indices (CAPE, K Index, Total Totals Index, and Lifted Index), together with low-level convergence and updraft fields from the WRF-ARW model, to identify the development of convective cells influenced by the Bandung Basin’s topography. The results reveal a distinct spatiotemporal evolution of convection across mountainous and valley regions. In the early phase, convection first emerged over mountainous areas, driven by a gradual increase in atmospheric instability and low-level convergence, before developing over the valley. The forecasted stability indices show a rising trend 2–5 hours before the onset of thunderstorms and heavy rainfall in the Pagarsih area. At the mature stage, mountain convection was mainly initiated by solar radiation heating, while valley convection was predominantly triggered by mechanical forcing, characterized by a sudden surge in low-level convergence, instability indices, and updraft, leading to more explosive convective development. During dissipation, convection weakened in both regions; however, mountainous areas exhibited stronger convective recovery, indicating higher sensitivity to surface reheating.